Polymerization shrinkage: effects of boundary conditions and filling technique of resin composite restorations - Loguercio, A. D.; Reis, A.; Schroeder, M.; Balducci, I; Versluis, A.; Ballester, R. Y. (Elsevier B.V., 2004)
Objective: To evaluate the linear polymerization shrinkage (LPS) and the effect of polymerization shrinkage of a resin composite and resin-dentin bond strength under different boundary conditions and filling techniques.Methods: Two cavities (4 x 4 x 2 MM) were prepared in bovine incisors (n = 30). The teeth were divided into three groups, according to boundary conditions: In group TE, the total-etch technique was used. In group EE, only enamel was conditioned, and in group NE, none of the watts of the cavities were conditioned. A two-step adhesive system was applied to all cavities. The resin composite was inserted in one (B) or three increments (1), and tight-cured with 600 mW/cm(2) (80 s). The LPS (%) was measured in the top-bottom direction, by placing a probe in contact with resin composite during curing. Enamel and total mean gap widths were measured (400 x) in three slices obtained after sectioning the restorations. Then, the slices were sectioned again, either to obtain sticks from the adhesive interface from the bottom of the cavity or to obtain resin composite sticks (0.8 mm(2)) to be tested for tensile strength (Kratos machine, 0.5 mm/min). The data was subjected to a two-way repeated measures ANOVA and Tukey's test for comparison of the means (alpha = 0.05).Results: the highest percentage of LPS was found for the TE when bulk fitted, and the lowest percentage of LPS was found in the Hand NE when incrementally fitted. The resin dentin bond strength was higher and the total mean gap width was tower for TE group; no significant effect was detected for the main factor fitting techniques. No difference was detected for the tensile strength of resin composite among the experimental groups.Conclusions: the filling technique is not able to minimize effects of the polymerization shrinkage, and bonding to the cavity watts is necessary to assure reduced mean gap width and high bond strength values. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: polymerization shrinkage; boundary conditions; filling technique; incrementally technique; microtensite test; gap; tensile strength; resin-dentin bond strength; dentin adhesion